Contesting the framing of bioeconomy policy in Germany: the NGO perspective - Riemann, Lena; Giurca, Alexandru; Kleinschmit, Daniela (Journal of environmental policy and planning, 2022)
Civil society has so far been little involved in bioeconomy discussions. In 2019, German non-governmental organizations (NGOs) concerted their criticism towards the bioeconomy policy in Germany in two joint statements. Assuming that such developments may further polarize the societal debate on bioeconomy, we set out to understand the NGOs’ criticism, as well as their framing of bioeconomy as opposed to the bioeconomy understanding at the federal level. We find that in many cases the bioeconomy frames emerging from policy documents differ substantially from those of NGOs. Despite lacking a common bioeconomy vision, NGOs agree on the same existing set of problems which are mainly related to the neoliberal (green) growth narrative advocated in federal policy documents. Drawing on deliberative governance concepts, we discuss ways how both NGOs and policymakers can bring bioeconomy into the contemporary public debate and thus allow for different, and perhaps more diverse interpretations of the bioeconomy.
Gesehen am 20.07.2022